Modeling Dynamic Procurement Auctions of Standardized Supply Contracts in Electricity Markets including Bidders Adaptation (2015)
Descendant Clock Auctions have been increasingly used in power markets. Traditional approaches are focused on discovering the bidders’ best response but neglecting the bidders’ adaptation. This paper presents an algorithm based on decision theory to estimate the bidders’ behavior along the auction. The proposed model uses portfolio concepts and historical data of spot market to estimate a long term contract supply curve. This model was applied to evaluate the Colombia’s Organized Market (MOR). Demand curve parameters and round size were varied to evaluate their impact over auction outputs. Results show that demand curve has a quite small impact over bidders’ decisions and round size management is useful to avoid non-competitive bidders’ behavior. In addition, it is shown that auction’s starting prices strongly influence auction’s clearing prices. These results are extremely helpful to design market structures in power markets.